Pengembangan Produk Dan Proses Produksi Minuman Orumy (Olahan Rumput Laut) di UD Inokam Putat Jaya - Winarti, Sri; Anggreini, Riski Ayu (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
The closure of the ?Gang Dolly? localization by the Mayor of Surabaya Tri Rismaharini to save the Surabaya city some time ago, had a positive and negative impact on aspects of life in the area. Closure of localization will turn off the economic wheel in the region. Thousands of new unemployed who emerged after the closure will cause new problems in the Surabaya city. This encourages some people, especially the Putat Jaya Surabaya area to start new businesses that can be used as a source of income to family needs. One of the residents who was moved to start a new business was Mariyani's mother, a resident of Jl. Putat Jaya 3A no. 28 Surabaya. He along with 3 of his friends, pioneered a soft drink business from Spinosum seaweed which was given the ORUMY. Some problems UD INOKAM include; ORUMY beverage production process without sterilization stages, so the product is less durable, the food labeling system is not in accordance with the legislation. Training on the development of seaweed juice drink processing without preservatives has been carried out by replacing plastic bottles with glass bottles. Diversification of seaweed processing into ice cream and jelly drink has been carried out in particular the UD INOKAM business group. In this program also provided assistance tools namely ice cream maker and cup sealer to partners.